2021
DOI: 10.1007/s10818-021-09310-2
|View full text |Cite
|
Sign up to set email alerts
|

Los Angeles County SARS-CoV-2 Epidemic: Critical Role of Multi-generational Intra-household Transmission

Abstract: We observed wide variation in the incidence of confirmed COVID-19 cases in 300 communities making up Los Angeles County, the largest county by population in the United States. The surge in incidence from October 19, 2020 to January 10, 2021, accounting for two-thirds of all confirmed cases since the start of the epidemic, was concentrated in communities with a high prevalence of multi-generational households. This indicator of household structure was a more important predictor of the surge in incidence than th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…While this work has focused on demonstrating the substantial heterogeneity in risk probabilities and IFR across subpopulations, it employs a single-population epidemic model. LAC is a large county consisting of many composing cities and communities, each with their own epidemic processes unfolding at different rates [48]. Extreme disparities in infection incidence and mortality have been observed for different communities within LAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this work has focused on demonstrating the substantial heterogeneity in risk probabilities and IFR across subpopulations, it employs a single-population epidemic model. LAC is a large county consisting of many composing cities and communities, each with their own epidemic processes unfolding at different rates [48]. Extreme disparities in infection incidence and mortality have been observed for different communities within LAC.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will develop multi-population models that estimate subpopulation-stratified probabilities of infection, of illness progression, and IFR, accounting for key risk factors of both exposure to infection and severe illness given infection. Risk factors for exposure are not limited to age and health conditions, but also include more diverse socioeconomic factors including occupation and essential worker status, neighborhood of residence, housing overcrowding, multigenerational households, economic status, and access to PPE [48][49][50][51][52]. In the meantime, the subpopulation-stratified estimates of disease progression and IFR produced using the framework presented here can be used to evaluate policy decisions that may involve both population-wide interventions and interventions that target specific subpopulations at risk of developing severe illness given infection, for example isolating or prioritizing vaccination for the elderly or those with other health-related risk factors [16].…”
Section: Discussionmentioning
confidence: 99%
“…13 Accordingly, in all likelihood, SARS-CoV-2 infections were already occurring by mid-February in every one of the five boroughs of a city of over 8 million inhabitants. This pattern of early rapid, widespread dispersion is sharply distinguishable from the gradual radial geographic expansion of COVID-19 cases observed in the earliest days of epidemic in Los Angeles County, 14 a comparable sized jurisdiction with 10 million inhabitants.…”
Section: Early Rapid Widespread Community Transmissionmentioning
confidence: 81%
“…We relied upon the five-year (2015-2019) public use microsample of the U.S. Census Bureau's American Community (ACS) 65 to estimate the proportion of households in New York City that were at risk for multi-generational transmission of SARS-CoV-2. Following an earlier study of intra-household transmission in Los Angeles County, 14 we defined an at-risk household as having at least 4 persons, of whom at least one person was 18-34 years of age and at least one other person was at least 50 years of age. Based upon a subsample of 148,686 New York City households in the 5-year ACS database, we found that 18.3 percent of households satisfied this criterion.…”
Section: Prevalence Of At-risk Multi-generational Householdsmentioning
confidence: 99%
See 1 more Smart Citation